Black Los Angeles : American dreams and racial realities - Hunt, Darnell M.; Ramón, Ana-Christina (New York University Press, 2010)
Los Angeles is well-known as a temperate paradise with expansive beaches and mountain vistas, a booming luxury housing market, and the home of glamorous Hollywood. During the first half of the twentieth century, Los Angeles was also seen as a mecca for both African Americans and a steady stream of migrants from around the country and the world, transforming Los Angeles into one of the world's most diverse cities. The city has become a multicultural maze in which many now fear that the political clout of the region's large black population has been lost. Nonetheless, the dream of a better life.